UNDERSTANDING OF TPACK CANDIDATES FOR TEACHER TRAINING AND EDUCATION FACULTY OF UNIVERSITAS MUHAMMADIYAH TANGERANG - Iman Nurjaman; Titi Rachmi (Peneliti.net, 2019)
This study aims to determine the understanding of TPACK candidates for FKIP UMT teachers. This study uses a quantitative approach with survey research methods. Instrument to collect data using questionnaires distributed online using google form to students of five study programs at FKIP UMT, namely PGPAUD, PGSD, Indonesian Language, English and Mathematics. Based on the results of the study, this is indicated by the highest level of understanding on 60% and 58.9% practical teaching indicators on subject content and tends to be lower on other indicators. The conclusion of this study is that prospective teachers of FKIP UMT have a tendency to understand the TPACK.